2022
DOI: 10.3390/en15051944
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Hybrid Electric Architectures for Specialized Agricultural Tractors

Abstract: In this work, a comparative numerical analysis between the performance of a conventional specialized orchard tractor and those of three different hybrid electric tractor configurations is presented. The aim was to compare several powertrain configurations in the same working scenarios derived from field measurements. Peak power capabilities and endurance were numerically tested with specific load scenarios involving both transportation mission profiles and field activities with external implements powered thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Indeed, the use of a diesel engine within its best efficiency range is surely the most direct method to limit diesel fuel consumption. In this regard, the investigation of alternative powertrains and propulsion systems is essential to pursue carbon containment [55,56]. Improvements in tractor transmission could lead to the optimization of tractor idle phases other than diesel fuel-rate reduction.…”
Section: Global Resultsmentioning
confidence: 99%
“…Indeed, the use of a diesel engine within its best efficiency range is surely the most direct method to limit diesel fuel consumption. In this regard, the investigation of alternative powertrains and propulsion systems is essential to pursue carbon containment [55,56]. Improvements in tractor transmission could lead to the optimization of tractor idle phases other than diesel fuel-rate reduction.…”
Section: Global Resultsmentioning
confidence: 99%
“…The European Innovation Partnership Agricultural Productivity and Sustainability's SunBot project is an illustration of this strategy in action (EIP-AGRI). The project, which started in late 2018, has focused on automating a solar-powered tractor and mower for efficient utilization of resources in berry orchards [ 27 ]. The goal of the project is to automate an emission-free electrical tractor, which eventually will lead to improved harvest quality.…”
Section: Significant Technological Advancements In Digital Agriculturementioning
confidence: 99%
“…Labor shift from repetitive tasks to high-skilled engineering jobs and the imbalanced adoption of agri-technologies by farmers is expected to create social implications. Advanced intelligence and decision-making capabilities of robots results in debates about moral aspects and, overall, who has the responsibility for these actions [ 27 ]. In addition, the high cost of advanced technologies and the need for resources and infrastructure to implement robotics in the field will present significant feasibility challenges to the widespread adoption of agricultural robotics.…”
Section: Significant Technological Advancements In Digital Agriculturementioning
confidence: 99%
“…Nowadays, LIBs technology is experiencing rapid growth, driven by the decarbonization challenge and the spread of LIBs in new fields like automotive, and stationary energy storage [17,18,19,20,21,22]. It is demonstrated that mechanical fracture is among the main causes of aging and performance decay in LIBs [23].…”
Section: Introductionmentioning
confidence: 99%